Manual de procesos y procedimientos como soporte para la gestión administrativa en la Fundación Centro de Apoyo y Solidaridad Alianza - Rizo Macías, Carolina Selena (2019)
The objective of this research was to generate processes and procedures in the Alianza Support and Solidarity Center Foundation as a support to administrative management, to carry out this research three methodological phases were executed, first a diagnosis of the current situation was made in the Foundation contextualized to the scope of the processes that take place in it, by means of the application of information gathering techniques which are the interview, survey and observation, processing and analyzing the obtained data; as a second aspect the processes were described through the application of techniques that allow its detailed characterization, registering the information of the object of study in the process file, to elaborate and define the map structure and process the flow diagram, as the last phase the process and procedures manual was developed in the Foundation Support Center and Solidaridad Alianza determining its contribution to the administrative management and structure and proceeding to elaborate said manual, concluding that the manual of processes and procedures serves as a guide for the development of the functions and the good performance of each subordinate contributing in this way to the improvement of the administrative management of the institution.